Brass Art: A house within a house within a house within a house. (1st September 2014) - Lewis, Chara; Mojsiewicz, Kristin; Pettican, Anneké
Performances from Brass Art (Lewis, Mojsiewicz, Pettican), captured at the Freud Museum, London, using Kinect laser scanning and Processing, reveal an intimate response to spaces and technologies. 'A house within a house within a house within a house' links historical and cultural representations of the double, the unconscious and the uncanny to this artistic practice. The new moving-image and sonic works form part of a larger project to inhabit the writing rooms of influential authors, entitled 'Shadow Worlds | Writers' Rooms'.